Toxoplasmosis in patients of the Hospital Obrero de Lima - Cornejo Donayre, Alberto (1971)
He has conducted research to detect specific antibodies to Toxoplasma in 32 hospital patients Obrero de Lima , of which 13 were chosen at random among hospitalized in General Medicine Services ; 15 came from the Department of Ophthalmology and had symptoms and / or signs of toxoplasmosis and 4 Obstetrics . Are included 25 men and 7 women. The complement fixation reaction (RFC ) was used , according to the technique 50% hemolysis Bozicevich and hemagglutination reaction ( AHR) , the microtitration plate technique . Toxoplasma antigen used was provided by the National Communicable Disease Center in Atlanta, Georgia. In 15 ( 46.87 %) , serology was positive ; of these, 8 were between 21 and 30 years old and 5 between 31 and 50 , ie at the stage of greater work capacity. 4 obstetric symptoms, 3 had positive serology and of them, a seven pregnancies referred with symptoms of threatened abortion, 4 of which ended in abortion and the other , 6 of which 3 pregnancies ended in abortion ; third filed chorioretinitis and retinal detachment . Serology was positive in 5 of the 12 men with symptoms and / or signs of toxoplasmosis. In 2, severe unilateral uveitis , retinal hemorrhages , nodules Koeppe and Busacca and in 3 chorioretinitis , retinal detachment and a divergent strabismus was found. In 13 men and 3 women who had no symptoms and signs , there were 7 positive . It has tried to show not only the clinical and epidemiological importance of this dissemination and parasites, but also the severity of obstetric pathology and cause eye injuries among workers insured Lima.